Extractive Bioconversion of L-Phenylalanine to 2-Phenylethanol Using Polypropylene Glycol 1500 - Hua, Dong-Liang; Liang, Xiao-Hui; Che, Cheng-Chuan; Zhang, Xiao-Dong; Zhang, Jie; Li, Yan; Xu, Ping (Asian Journal of Chemistry, 2013)
Product cytotoxicity was a bottleneck in biotechnological production of 2-phenylethanol from L-phenylalanine. In this study, polypropylene glycol 1500 (PPG 1500) was firstly used as an extractant in the extractive bioconversion of L-phenylalanine by strain Saccharomyces cerevisiae P-3. About 4.8 g L-1 2-phenylethanol was obtained from 7 g L-1 L-phenylalanine in flask experiment within 36 h, with a high molar yield of 92.7 %. Compared to conventional bioconversion without addition of extractant, the yield was improved by 26.3 %. In a fed-batch extractive bioconversion, the highest concentration of 2-phenylethanol in the organic phase exceeded 22 g L-1 and the total concentration in both aqueous and organic phases reached 7.5 g L-1. The results showed that the process with polypropylene glycol 1500 as an extractant might have the potential in bioproduction of 2-phenylethanol.